Method for manufacturing thermoelectric conversion element
The use of a pattern frame to form thermoelectric element layers addresses shape controllability and integration issues, resulting in improved thermoelectric performance and reduced manufacturing costs.
Patent Information
- Application Number
- JP2024173932
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-08-28
- Filing Date
- 2024-10-02
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2039-08-27
AI Technical Summary
Existing methods for manufacturing thermoelectric conversion elements, such as screen printing, result in insufficient shape controllability of the thermoelectric element layer, leading to issues like bleeding, collapse, and poor electrical and physical connectivity, which affect thermoelectric performance and integration.
A method involving a pattern frame with spaced openings on a substrate, filled with a thermoelectric semiconductor composition, followed by drying and peeling off the frame to form a thermoelectric element layer, allowing for excellent shape controllability and high integration.
The method enables thermoelectric elements with improved shape controllability and high integration, reducing thermal resistance and variations in resistance values, thereby enhancing thermoelectric performance and reducing manufacturing costs.
Smart Images

Figure 2025000945000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a thermoelectric conversion element. [Background technology]
[0002] 2. Description of the Related Art Conventionally, as one of the means for effectively utilizing energy, there has been a device that directly converts thermal energy into electrical energy and vice versa using a thermoelectric conversion module having a thermoelectric effect such as the Seebeck effect or the Peltier effect. Among these, the use of so-called π-type thermoelectric conversion elements as the thermoelectric conversion elements is known. The π-type is usually configured by providing a pair of electrodes spaced apart from each other on a substrate, for example, by providing a P-type thermoelectric element on one electrode and an N-type thermoelectric element on the other electrode, also spaced apart from each other, and connecting the upper surfaces of both thermoelectric elements to the electrodes of the opposing substrate. Also, the use of so-called in-plane type thermoelectric conversion elements is known. The in-plane type is usually configured by arranging multiple thermoelectric elements so that the N-type thermoelectric elements and the P-type thermoelectric elements are alternately arranged, and for example, by connecting the lower electrodes of the thermoelectric elements in series.
[0003] In recent years, there has been a demand for thinner thermoelectric conversion elements, improved thermoelectric performance including higher integration, etc. Patent Document 1 discloses a method of directly forming a pattern of a thermoelectric element layer by a screen printing method or the like using a thermoelectric semiconductor composition containing a resin or the like as the thermoelectric element layer, taking into consideration the need for thinner layers. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2016 / 104615 Summary of the Invention [Problem to be solved by the invention]
[0005] However, as in Patent Document 1, in the method of forming a thermoelectric element directly on an electrode or a substrate as a pattern layer by screen printing or the like using a thermoelectric semiconductor composition made of a thermoelectric semiconductor material, a heat-resistant resin, etc., the shape controllability of the obtained thermoelectric element layer is insufficient, and bleeding occurs at the end of the thermoelectric element layer at the electrode interface or the substrate interface, or the shape of the thermoelectric element layer is distorted, and it is not possible to control it to a desired shape. For example, when forming the above-mentioned π-type thermoelectric conversion element, sufficient electrical and physical bonding may not be obtained between the upper surface of the obtained thermoelectric element layer and the electrode surface on the opposing substrate. In this case, the inherent thermoelectric performance of the thermoelectric element layer cannot be fully brought out, such as an increase in thermal resistance, and it is necessary to increase the number of P-type thermoelectric element layer-N-type thermoelectric element layer pairs in order to obtain a predetermined power generation performance or cooling performance. Furthermore, when highly integrating π-type thermoelectric conversion elements, the variation in resistance value of each of the multiple P-type thermoelectric element layer-N-type thermoelectric element layer pairs may increase, or adjacent thermoelectric element layers may come into contact with each other. Similarly, when the configuration of the in-plane type thermoelectric conversion element described above is highly integrated, the ends of the P-type thermoelectric element layer and the N-type thermoelectric element layer may interdigitate with each other, making the interface unclear. This may result in variations in the resistance values of multiple P-type thermoelectric element layer-N-type thermoelectric element layer pairs as well as variations in the temperature difference or output between each junction between adjacent P-type thermoelectric element layers and N-type thermoelectric element layers.
[0006] In view of the above, an object of the present invention is to provide a method for manufacturing a thermoelectric conversion element that has a thermoelectric element layer with excellent shape controllability and allows for high integration. [Means for solving the problem]
[0007] As a result of intensive research aimed at solving the above problems, the inventors have discovered a method for producing a thermoelectric conversion element having a thermoelectric element layer with excellent shape controllability and capable of being highly integrated, by providing a pattern frame having spaced openings on a substrate, filling the openings with a thermoelectric semiconductor composition containing a thermoelectric semiconductor material, drying the composition to form a thermoelectric element layer, and then peeling the pattern frame from the substrate, thereby completing the present invention. That is, the present invention provides the following (1) to (13). (1) A method for manufacturing a thermoelectric conversion element including a thermoelectric element layer made of a thermoelectric semiconductor composition containing a thermoelectric semiconductor material on a substrate, the method comprising the steps of: providing a pattern frame having an opening on the substrate; filling the opening with the thermoelectric semiconductor composition; drying the thermoelectric semiconductor composition filled in the opening to form a thermoelectric element layer; and peeling off the pattern frame from the substrate. (2) The method for producing a thermoelectric conversion element according to (1) above, further comprising a step of annealing the thermoelectric element layer. (3) The method for producing a thermoelectric conversion element according to (2) above, wherein the annealing temperature is 250 to 600°C. (4) The method for producing a thermoelectric conversion element according to (2) or (3) above, further comprising the step of peeling off the chips constituting the thermoelectric element layer after the annealing treatment. (5) The method for producing a thermoelectric conversion element according to any one of the above (1) to (4), wherein the substrate is a polyimide film, a polyamide film, a polyetherimide film, a polyaramid film, or a polyamideimide film. (6) The method for producing a thermoelectric conversion element according to any one of (1) to (5) above, wherein the pattern frame contains stainless steel, copper, aluminum, or iron. (7) The method for producing a thermoelectric conversion element according to any one of (1) to (6) above, wherein the pattern frame contains a ferromagnetic material. (8) The method for producing a thermoelectric conversion element according to any one of (1) to (7) above, wherein a release layer is included on a wall surface of the opening of the pattern frame. (9) The method for producing a thermoelectric conversion element according to any one of (1) to (8) above, further comprising the step of fixing the pattern frame to the substrate using a magnet. (10) The method for producing a thermoelectric conversion element according to any one of (1) to (9) above, wherein the thermoelectric semiconductor composition further contains a heat-resistant resin, and an ionic liquid and / or an inorganic ionic compound. (11) The method for producing a thermoelectric conversion element according to any one of (1) to (10) above, wherein the thermoelectric semiconductor material is a bismuth-tellurium based thermoelectric semiconductor material, a telluride based thermoelectric semiconductor material, an antimony-tellurium based thermoelectric semiconductor material, or a bismuth selenide based thermoelectric semiconductor material. (12) The method for producing a thermoelectric conversion element according to (10) above, wherein the heat-resistant resin is a polyimide resin, a polyamide resin, a polyamideimide resin, or an epoxy resin. (13) The method for producing a thermoelectric conversion element according to any one of (1) to (12) above, wherein the opening has one or more shapes selected from the group consisting of an irregular shape, a polyhedron, a truncated cone, an elliptical truncated cone, a cylindrical shape, and an elliptical cylindrical shape. Effect of the Invention
[0008] According to the present invention, it is possible to provide a method for manufacturing a thermoelectric conversion element having a thermoelectric element layer with excellent shape controllability and capable of being highly integrated. [Brief description of the drawings]
[0009] [Figure 1] 1A to 1C are explanatory views showing an example of steps according to a method for producing a thermoelectric conversion element of the present invention in the order of steps. [Diagram 2] FIG. 2 is a configuration diagram for explaining an example of a pattern frame used in the manufacturing method of a thermoelectric conversion element of the present invention. [Diagram 3] FIG. 1 is a cross-sectional view showing an example of a π-type thermoelectric conversion element obtained by steps according to a manufacturing method of a thermoelectric conversion element of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [Method of manufacturing thermoelectric conversion element] The method for manufacturing a thermoelectric conversion element of the present invention is a method for manufacturing a thermoelectric conversion element including a thermoelectric element layer made of a thermoelectric semiconductor composition containing a thermoelectric semiconductor material on a substrate, and is characterized in that it includes the steps of providing a pattern frame having an opening on the substrate, filling the opening with the thermoelectric semiconductor composition, drying the thermoelectric semiconductor composition filled in the opening to form a thermoelectric element layer, and peeling off the pattern frame from the substrate. In the method for manufacturing a thermoelectric conversion element of the present invention, a pattern frame having spaced openings is provided on a substrate, a thermoelectric semiconductor composition containing a thermoelectric semiconductor material is filled into the openings, the pattern frame is dried, and the pattern frame is peeled off from the substrate, thereby forming a thermoelectric element layer with excellent shape controllability. The method for producing a thermoelectric conversion element of the present invention is preferably used to form a π-type thermoelectric conversion element and an in-plane type thermoelectric conversion element. In the configuration of the π-type thermoelectric conversion element, sufficient electrical and physical bonding is obtained between the upper surface of the obtained thermoelectric element layer and the electrode surface on the opposing substrate, and an increase in thermal resistance, etc. is suppressed, and the thermoelectric performance inherent to the thermoelectric element layer can be fully brought out. In addition, when integrating the configuration of the π-type thermoelectric conversion element, the excellent shape controllability suppresses the variation in the resistance value of each of the multiple P-type thermoelectric element layer-N-type thermoelectric element layer pairs, and adjacent thermoelectric element layers do not come into contact with each other, enabling high integration. In addition, when integrating the configuration of the in-plane type thermoelectric conversion element, excellent shape controllability prevents the ends of adjacent P-type thermoelectric element layers and N-type thermoelectric element layers from interdigitating with each other to make the interface unclear, thereby suppressing variations in the resistance values of multiple P-type thermoelectric element layer-N-type thermoelectric element layer pairs. In addition, the occurrence of temperature differences or output between each junction between adjacent P-type thermoelectric element layers and N-type thermoelectric element layers is stabilized, enabling high integration. On the other hand, even if the obtained thermoelectric element layer is transferred to another substrate having electrodes as it is to form a π-type thermoelectric conversion element or an in-plane type thermoelectric conversion element, or even if each chip is placed on the electrode of the substrate as a chip constituting the thermoelectric element layer to form a π-type thermoelectric conversion element or an in-plane type thermoelectric conversion element, the bonding with the electrode surface constituting the thermoelectric conversion element is improved, the decrease in thermoelectric performance due to the increase in thermal resistance is suppressed, and the thermoelectric performance inherent to the thermoelectric element layer is expressed. As a result, the number of thermoelectric element layers required to obtain a predetermined thermoelectric performance can be reduced, leading to a reduction in manufacturing costs. At the same time, this leads to lower power consumption in cooling and higher output in power generation. Regarding integration, the use of a thermoelectric element layer with excellent shape controllability allows for high integration.
[0011] In this specification, "opening" refers to a plurality of openings spaced apart from one another in an inner region of the entire region of the pattern frame described below, each of which has a planar shape (when the pattern frame on the substrate is viewed from the top) that extends to the substrate surface in the thickness (depth) direction of the pattern frame. For example, when the planar shape of an opening is rectangular, the shape of the opening is usually approximately rectangular, although this varies depending on the method of forming or processing the pattern frame. Similarly, for example, when the planar shape of an opening is circular, the shape of the opening is usually approximately cylindrical. The shape of the openings in the pattern frame is not particularly limited, and any desired shape can be used, as described below. Hereinafter, the method for producing a thermoelectric conversion element of the present invention will be described with reference to the drawings.
[0012] FIG. 1 is an explanatory diagram showing an example of steps according to a manufacturing method of a thermoelectric conversion element of the present invention in the order of steps, in which (a) is a cross-sectional view showing an embodiment in which a pattern frame is opposed to a substrate, (b) is a cross-sectional view after the pattern frame has been formed on the substrate, (c) is a cross-sectional view after the openings of the pattern frame have been filled with a thermoelectric element layer, and (d) is a cross-sectional view showing an embodiment in which the pattern frame has been peeled off from the filled thermoelectric element layer to obtain only the thermoelectric element layer.
[0013] Fig. 3 is a cross-sectional view showing an example of a π-type thermoelectric conversion element obtained by steps according to the manufacturing method of a thermoelectric conversion element of the present invention. In Fig. 1(a), except that an electrode 12a is provided on a substrate (on a substrate 11a in Fig. 3), an N-type thermoelectric element layer 14a and a P-type thermoelectric element layer 14b are formed by steps similar to those in Fig. 1(b) to (d), and then the upper surfaces of the N-type thermoelectric element layer 14a and the P-type thermoelectric element layer 14b are joined to a counter electrode 12b on a counter substrate 11b, thereby manufacturing a π-type thermoelectric conversion element.
[0014] <Pattern frame formation process> The pattern frame forming step is a step of providing a pattern frame on a substrate. For example, in (a) of FIG. 1, a pattern frame 2 made of stainless steel 2' described below and having an opening 3s, an opening 3, and an opening depth (pattern frame thickness) 3d is opposed to a substrate 1, and in (b), the pattern frame 2 is provided on the substrate 1. In the present invention, the pattern frame may be provided by directly forming it on the substrate, but from the viewpoint of peeling the pattern frame from the substrate in the pattern frame peeling step described below, it is usually preferable to provide the pattern frame by placing and fixing a pattern frame formed in advance on the substrate.
[0015] (Pattern Frame) In the method for manufacturing a thermoelectric conversion element of the present invention, a pattern frame having an opening is provided on a substrate.
[0016] 2 is a configuration diagram for explaining an example of a pattern frame used in the manufacturing method of a thermoelectric conversion element of the present invention, where (a) is a plan view of the pattern frame and (b) is a cross-sectional view of the pattern frame when cut along A-A' in (a). The pattern frame 2 is made of stainless steel 2' and has an opening 3s and an opening 3 with an opening depth (pattern frame thickness) 3d.
[0017] The arrangement, number and dimensions of the openings and apertures included in the pattern frame, including the distance between the openings, are not particularly limited and are appropriately adjusted according to the shape and arrangement of the thermoelectric element layer. The shape of the opening is not particularly limited, and a desired shape can be used. Preferably, the opening is one or more shapes selected from the group consisting of an indefinite shape, a polyhedron, a circular truncated cone, an elliptical truncated cone, a cylindrical shape, and an elliptical cylindrical shape. Examples of the polyhedron include a cube, a rectangular parallelepiped, and a truncated pyramid shape. Since the pattern frame is easily formed or processed, a cube, a rectangular parallelepiped, a truncated pyramid, and a cylindrical shape are more preferable. Among these, a rectangular parallelepiped or a cube is more preferable from the viewpoint of the shape of the thermoelectric element layer and the thermoelectric performance. In FIG. 2, the opening 3s is square, and the opening 3 is substantially cubic (not shown), with a total of 4×4 openings and openings.
[0018] Examples of materials constituting the pattern frame include single metals such as copper, silver, iron, nickel, chromium, and aluminum, and alloys such as stainless steel and brass. Preferably, the material contains stainless steel, copper, aluminum, or iron. From the viewpoint of ease of forming the pattern frame, stainless steel and copper are more preferable. In addition, stainless steel is written as SUS (Steel Special Use Stainless) in JIS and is defined as "an alloy steel containing iron as the main component and Cr and Ni for the purpose of improving corrosion resistance, generally with a C content of 1.2% or less and a Cr content of 10.5% or more." Examples of stainless steel include ferritic stainless steel (JIS standard SUS430 series, etc.) and austenitic stainless steel (JIS standard SUS304 series and SUS316 series, etc.).
[0019] It is also preferable that the pattern frame contains a ferromagnetic material, whereby when, for example, a magnet is disposed on the surface of the substrate opposite to the pattern frame, the pattern frame can be easily fixed via the substrate. Examples of ferromagnetic materials include iron, nickel, cobalt, and alloys thereof, as well as ferritic stainless steel. In addition, an alloy of at least one element selected from iron, nickel, cobalt, manganese, and chromium with at least one element selected from platinum, palladium, iridium, ruthenium, and rhodium can be used. The properties of the ferromagnetic material can be changed by changing the composition, heat treatment, and the like. Among these, ferritic stainless steel is preferred from the viewpoints of versatility, fixing strength, ease of attachment and detachment, damage to the substrate, and heat resistance. As the ferritic stainless steel, SUS430 is preferred. The magnet is not particularly limited as long as the pattern frame does not shift during the manufacture of the thermoelectric element layer, but a permanent magnet or an electromagnet can be used. For example, a permanent magnet is a ferrite magnet (components: BaO 6Fe2O3, SrO 6Fe2O3, magnetic flux density 0.4 Wb / m 2 ), neodymium magnet (component: Nd2Fe 14 B, magnetic flux density 1.2Wb / m 2 ), samarium magnet (component: SmCo5, magnetic flux density 1.2 Wb / m 2 ), praseodymium magnets (PrCo5), samarium iron nitrogen magnets, etc. can be used. Among these, ferrite magnets and neodymium magnets are more preferable from the viewpoints of versatility, fixing strength, damage to the substrate, and heat resistance.
[0020] The pattern frame is formed from the material. The method for forming the pattern frame is not particularly limited, but examples of the method include a method in which the sheet-like material is processed in advance into a predetermined pattern shape by known physical or chemical treatments, mainly photolithography, or a combination of these, laser processing, electric discharge processing, milling, computer numerical control processing, water jet processing, and punching. Alternatively, a method may be used in which a layer made of the above-mentioned material on which no pattern has been formed is processed into a predetermined pattern shape by a known physical or chemical treatment, mainly based on the above-mentioned photolithography method, or a combination of these, using a dry process such as PVD (physical vapor deposition) such as vacuum deposition, sputtering, or ion plating, or a CVD (chemical vapor deposition) such as thermal CVD or atomic layer deposition (ALD), or a wet process such as various coatings or electrodeposition such as dip coating, spin coating, spray coating, gravure coating, die coating, or doctor blade, or a silver halide method. In the present invention, from the viewpoint of process simplicity and pattern accuracy, it is preferable to form a predetermined pattern by subjecting the sheet-like material to a known chemical treatment mainly based on photolithography, for example, by wet etching the patterned portion of the photoresist and removing the photoresist, or by laser processing.
[0021] The thickness of the pattern frame depends on the thickness of the thermoelectric element layer and is adjusted appropriately, but is preferably 100 nm to 1000 μm, more preferably 1 to 600 μm, further preferably 10 to 400 μm, and particularly preferably 10 to 300 μm. If the thickness of the pattern frame is within this range, it is easy to obtain a pattern frame having an opening shape with excellent pattern accuracy.
[0022] (Release layer) It is preferable that the wall surface of the opening of the pattern frame used in the present invention contains a release layer, which has the function of easily peeling the formed thermoelectric element layer from the pattern frame. In this specification, "wall surface of an opening portion of a pattern frame" refers to the wall surface of the pattern frame that constitutes each opening portion provided in the pattern frame.
[0023] The release agent constituting the release layer is not particularly limited, and examples thereof include fluorine-based release agents (fluorine atom-containing compounds; for example, fluorine oil, polytetrafluoroethylene, etc.), silicone-based release agents (silicone compounds; for example, silicone oil, silicone wax, silicone resin, polyorganosiloxane having polyoxyalkylene units, etc.), wax-based release agents (waxes; for example, vegetable waxes such as carnauba wax, animal waxes such as wool wax, paraffins such as paraffin wax, polyethylene wax, oxidized polyethylene wax, etc.), higher fatty acids or salts thereof (for example, metal salts, etc.), higher fatty acid esters, higher fatty acid amides, mineral oils, etc. Among these, from the viewpoints of facilitating peeling after the formation of the thermoelectric element layer and after the annealing treatment and of making it easier to maintain the shape controllability of the thermoelectric element layer after peeling, fluorine-based release agents and silicone-based release agents are preferred, and from the viewpoint of peelability, fluorine-based release agents are more preferred.
[0024] The thickness of the release layer is preferably 10 nm to 5 μm, more preferably 50 nm to 1 μm, and further preferably 100 nm to 0.5 μm. When the thickness of the release layer is within this range, peeling after the formation of the thermoelectric element layer and after the annealing treatment becomes easy, and the shape controllability of the thermoelectric element layer after peeling is easily maintained.
[0025] The release layer is formed using the above-mentioned release agent. The method for forming the release layer includes various coating methods such as dip coating, spray coating, gravure coating, die coating, doctor blade, etc., for the pattern frame. The method is appropriately selected depending on the shape of the pattern frame, the physical properties of the release agent, etc.
[0026] <Pattern frame fixing process> The method for manufacturing a thermoelectric conversion element of the present invention preferably includes a step of fixing a pattern frame including the ferromagnetic body to the substrate using the above-mentioned permanent magnet. The method for fixing the pattern frame can be a known method. For example, the pattern frame including a ferromagnetic material is fixed to face a permanent magnet with a substrate interposed therebetween. The permanent magnet is appropriately adjusted depending on the type and thickness of the pattern frame and substrate, which are ferromagnetic materials, and the like.
[0027] (substrate) In the thermoelectric conversion element of the present invention, a resin film that does not affect the decrease in electrical conductivity or the increase in thermal conductivity of the thermoelectric element layer can be used as the substrate. Among them, a polyimide film, a polyamide film, a polyetherimide film, a polyaramid film, or a polyamideimide film is preferred because it has excellent flexibility, and even when a thin film of the thermoelectric element layer made of a thermoelectric semiconductor composition is annealed, the substrate does not thermally deform, and the performance of the thermoelectric element layer can be maintained, and it has high heat resistance and dimensional stability. Furthermore, a polyimide film is particularly preferred because it is highly versatile.
[0028] From the viewpoints of flexibility, heat resistance, and dimensional stability, the thickness of the resin film is preferably from 1 to 1000 μm, more preferably from 5 to 500 μm, and even more preferably from 10 to 100 μm. The resin film preferably has a 5% weight loss temperature of 300°C or higher, more preferably 400°C or higher, as measured by thermogravimetric analysis. The thermal dimensional change rate measured at 200°C in accordance with JIS K7133 (1999) is preferably 0.5% or lower, more preferably 0.3% or lower. The linear expansion coefficient in the planar direction measured in accordance with JIS K7197 (2012) is 0.1 ppm·°C or higher. -1 ~50ppm·℃ -1 and 0.1 ppm·℃ -1 ~30ppm·℃ -1 It is more preferable that:
[0029] In addition, the substrate used in the present invention may be glass, silicon, ceramic, or metal, from the viewpoint of performing annealing treatment at high temperatures. From the viewpoint of material cost and dimensional stability after heat treatment, it is more preferable to use glass, silicon, or ceramic. From the viewpoints of process and dimensional stability, the thickness of the substrate is preferably from 100 to 1200 μm, more preferably from 200 to 800 μm, and even more preferably from 400 to 700 μm. Incidentally, an electrode, which will be described later, may be formed on the substrate including the resin film.
[0030] In the manufacturing method of the present invention, as described below, when the obtained thermoelectric element layer is used as a chip constituting the thermoelectric element layer, it is preferable to use a transfer base material as the substrate. By using the transfer base material, the obtained thermoelectric element layer can be transferred, for example, onto the electrodes of another substrate in a lump as a chip constituting the thermoelectric element layer. Examples of the transfer substrate include glass, silicon, ceramic, metal, plastic, etc., each having a sacrificial layer. From the viewpoint of performing the annealing treatment at a high temperature, glass, silicon, ceramic, and metal are preferred, and from the viewpoints of adhesion to the sacrificial layer, material cost, and dimensional stability after heat treatment, glass, silicon, and ceramic are more preferred. The thickness of the transfer substrate is preferably from 100 to 1200 μm, more preferably from 200 to 800 μm, and even more preferably from 400 to 700 μm, from the viewpoints of process and dimensional stability. The sacrificial layer is provided on the transfer base material and has a function of easily peeling the obtained thermoelectric element layer from the transfer base material as a chip constituting the thermoelectric element layer. The material constituting the sacrificial layer is preferably a resin or a mold release agent. The resin is not particularly limited, but a thermoplastic resin or a curable resin can be used. The mold release agent constituting the sacrificial layer is not particularly limited, but a fluorine-based mold release agent (a fluorine atom-containing compound; for example, polytetrafluoroethylene, etc.), a silicone-based mold release agent (a silicone compound; for example, a silicone resin, a polyorganosiloxane having a polyoxyalkylene unit, etc.), a higher fatty acid or its salt (for example, a metal salt, etc.), a higher fatty acid ester, a higher fatty acid amide, etc. can be mentioned. The thickness of the sacrificial layer is preferably 10 nm to 10 μm, more preferably 50 nm to 5 μm, and further preferably 200 nm to 2 μm. When the thickness of the sacrificial layer is in this range, the thermoelectric element layer can be easily peeled off after the annealing treatment, and the thermoelectric performance of the thermoelectric element layer chip after peeling can be easily maintained.
[0031] (Electrode formation process) The method for producing a thermoelectric conversion element of the present invention may include an electrode forming step, which is a step of forming an electrode on a substrate. Examples of metal materials for the electrodes of the thermoelectric conversion element include copper, gold, nickel, aluminum, rhodium, platinum, chromium, palladium, stainless steel, molybdenum, tin, and alloys containing any of these metals. The thickness of the electrode layer is preferably 10 nm to 200 μm, more preferably 30 nm to 150 μm, and further preferably 50 nm to 120 μm. When the thickness of the electrode layer is within the above range, the electrical conductivity is high and the resistance is low, and sufficient strength as an electrode is obtained.
[0032] The electrodes are formed using the above-mentioned metal materials. Examples of the method for forming the electrode include a method in which an electrode without a pattern is provided on a substrate, and then processed into a predetermined pattern shape by known physical or chemical treatments, mainly photolithography, or a combination of these, or a method in which an electrode pattern is directly formed by screen printing, inkjet printing, or the like. Methods for forming an electrode without a pattern include dry processes such as PVD (physical vapor deposition) methods such as vacuum deposition, sputtering, and ion plating, or CVD (chemical vapor deposition) methods such as thermal CVD and atomic layer deposition (ALD), or wet processes such as various coating methods and electrodeposition methods such as dip coating, spin coating, spray coating, gravure coating, die coating, and doctor blade methods, silver halide plating, electrolytic plating, electroless plating, and lamination of metal foils, and are appropriately selected depending on the material of the electrode. The electrodes used in the present invention are required to have high electrical conductivity and high thermal conductivity in order to maintain thermoelectric performance, so it is preferable to use electrodes formed by plating or vacuum film formation. Vacuum film formation methods such as vacuum deposition and sputtering, as well as electrolytic plating and electroless plating are preferred because they can easily achieve high electrical conductivity and high thermal conductivity. Depending on the size and dimensional accuracy requirements of the formed pattern, a hard mask such as a metal mask can also be used to easily form a pattern.
[0033] <Thermoelectric semiconductor composition filling process> The thermoelectric semiconductor composition filling step is a step of filling the openings of the pattern frame on the substrate obtained in the pattern frame forming step with a thermoelectric semiconductor composition containing the thermoelectric semiconductor material. For example, in FIG. 1(c), it is a step of filling a thermoelectric semiconductor composition containing a P-type thermoelectric semiconductor material and a thermoelectric semiconductor composition containing an N-type thermoelectric semiconductor material into predetermined openings 3 having openings 3s of the pattern frame 2 made of stainless steel 2' prepared in (b). Methods for filling the openings of the pattern layer with the thermoelectric semiconductor composition include known methods such as screen printing, flexographic printing, gravure printing, spin coating, die coating, spray coating, bar coating, doctor blade, dispensing, etc. From the viewpoints of filling accuracy and production efficiency, it is preferable to use the screen printing, stencil printing, and dispensing methods.
[0034] <Thermoelectric element layer formation process> The thermoelectric element layer forming step is a step of drying the thermoelectric semiconductor composition containing the thermoelectric semiconductor material filled in the thermoelectric semiconductor composition filling step to form a thermoelectric element layer. For example, in Fig. 1(c), the thermoelectric semiconductor composition containing a P-type thermoelectric semiconductor material and the thermoelectric semiconductor composition containing an N-type thermoelectric semiconductor material filled in the opening 3 are dried to form a P-type thermoelectric element layer 4b and an N-type thermoelectric element layer 4a. As the drying method, a conventionally known drying method such as hot air drying, hot roll drying, infrared irradiation, etc. can be used. The heating temperature is usually 80 to 150° C., and the heating time varies depending on the heating method, but is usually several seconds to several tens of minutes. When a solvent is used in the preparation of the thermoelectric semiconductor composition, the heating temperature is not particularly limited as long as it is within a temperature range in which the solvent used can be dried.
[0035] (Thermoelectric element layer) The thermoelectric element layer (hereinafter sometimes referred to as "thin film of thermoelectric element layer") used in the present invention is made of a thermoelectric semiconductor composition containing a thermoelectric semiconductor material. Preferably, it is made of a thermoelectric semiconductor composition containing a thermoelectric semiconductor material (hereinafter sometimes referred to as "thermoelectric semiconductor fine particles"), a heat-resistant resin, and an ionic liquid and / or an inorganic ionic compound.
[0036] (Thermoelectric semiconductor materials) The thermoelectric semiconductor material used in the present invention, i.e., the thermoelectric semiconductor material contained in the thermoelectric element layer, is not particularly limited as long as it is a material that can generate a thermoelectromotive force by applying a temperature difference. For example, bismuth-tellurium-based thermoelectric semiconductor materials such as P-type bismuth telluride and N-type bismuth telluride; telluride-based thermoelectric semiconductor materials such as GeTe and PbTe; antimony-tellurium-based thermoelectric semiconductor materials; ZnSb, Zn3Sb 2、 Zinc-antimony thermoelectric semiconductor materials such as Zn4Sb3; silicon-germanium thermoelectric semiconductor materials such as SiGe; bismuth selenide thermoelectric semiconductor materials such as Bi2Se3; β-FeSi2, CrSi2, MnSi 1.73 Examples of thermoelectric semiconductor materials that can be used include silicide-based thermoelectric semiconductor materials such as Mg2Si; oxide-based thermoelectric semiconductor materials; Heusler materials such as FeVAl, FeVAlSi, and FeVTiAl; and sulfide-based thermoelectric semiconductor materials such as TiS2. Among these, bismuth-tellurium based thermoelectric semiconductor materials, telluride based thermoelectric semiconductor materials, antimony-tellurium based thermoelectric semiconductor materials, and bismuth selenide based thermoelectric semiconductor materials are preferred.
[0037] Furthermore, from the perspective of thermoelectric performance, it is more preferable that it is a bismuth-tellurium-based thermoelectric semiconductor material such as P-type bismuth telluride or N-type bismuth telluride. The P-type bismuth telluride has holes as carriers and a positive Seebeck coefficient. For example, Bi X Te3Sb 2-X represented by is preferably used. In this case, X is preferably 0 < X ≤ 0.8, more preferably 0.4 ≤ X ≤ 0.6. When X is greater than 0 and less than or equal to 0.8, the Seebeck coefficient and electrical conductivity increase, and the characteristics as a P-type thermoelectric element are maintained, which is preferable. Also, the N-type bismuth telluride has electrons as carriers and a negative Seebeck coefficient. For example, Bi2Te 3-Y Se Y represented by is preferably used. In this case, Y is preferably 0 ≤ Y ≤ 3 (when Y = 0: Bi2Te3), more preferably 0 < Y ≤ 2.7. When Y is 0 or more and 3 or less, the Seebeck coefficient and electrical conductivity increase, and the characteristics as an N-type thermoelectric element are maintained, which is preferable.
[0038] The thermoelectric semiconductor fine particles used in the thermoelectric semiconductor composition are those obtained by pulverizing the aforementioned thermoelectric semiconductor material to a predetermined size using a pulverizing device or the like.
[0039] The blending amount of the thermoelectric semiconductor fine particles in the thermoelectric semiconductor composition is preferably 30 to 99% by mass. More preferably, it is 50 to 96% by mass, and even more preferably, it is 70 to 95% by mass. When the blending amount of the thermoelectric semiconductor fine particles is within the above range, the Seebeck coefficient (absolute value of the Peltier coefficient) is large, the decrease in electrical conductivity is suppressed, and only the thermal conductivity decreases, so it exhibits high thermoelectric performance, and a film with sufficient film strength and flexibility can be obtained, which is preferable.
[0040] The average particle size of the thermoelectric semiconductor particles is preferably 10 nm to 200 μm, more preferably 10 nm to 30 μm, further preferably 50 nm to 10 μm, and particularly preferably 1 to 6 μm. Within the above range, uniform dispersion is facilitated and electrical conductivity can be increased. The method for pulverizing the thermoelectric semiconductor material to obtain thermoelectric semiconductor fine particles is not particularly limited, and the material may be pulverized to a predetermined size using a known fine pulverizing device such as a jet mill, ball mill, bead mill, colloid mill, or roller mill. The average particle size of the thermoelectric semiconductor particles was obtained by measurement using a laser diffraction particle size analyzer (Malvern, Mastersizer 3000) and was taken as the median value of the particle size distribution.
[0041] In addition, the thermoelectric semiconductor fine particles are preferably heat-treated in advance (the "heat treatment" here is different from the "annealing treatment" performed in the annealing treatment step in the present invention). By performing the heat treatment, the crystallinity of the thermoelectric semiconductor fine particles is improved, and further, the surface oxide film of the thermoelectric semiconductor fine particles is removed, so that the Seebeck coefficient or Peltier coefficient of the thermoelectric conversion material is increased, and the thermoelectric figure of merit can be further improved. The heat treatment is not particularly limited, but is preferably performed in an inert gas atmosphere such as nitrogen or argon, in a reducing gas atmosphere such as hydrogen, or under vacuum conditions with a controlled gas flow rate, before preparing the thermoelectric semiconductor composition, so as not to adversely affect the thermoelectric semiconductor fine particles, and more preferably in a mixed gas atmosphere of an inert gas and a reducing gas. The specific temperature conditions depend on the thermoelectric semiconductor fine particles used, but it is usually preferable to perform the heat treatment at a temperature below the melting point of the fine particles and at 100 to 1500°C for several minutes to several tens of hours.
[0042] (Heat-resistant resin) A heat-resistant resin is preferably used for the thermoelectric semiconductor composition used in the present invention, from the viewpoint of annealing the thermoelectric semiconductor material at a high temperature after forming the thermoelectric element layer. It acts as a binder between the thermoelectric semiconductor material (thermoelectric semiconductor fine particles), and can increase the flexibility of the thermoelectric conversion module, and also makes it easier to form a thin film by coating or the like. The heat-resistant resin is not particularly limited, but is preferably a heat-resistant resin that maintains various physical properties such as mechanical strength and thermal conductivity as a resin without being impaired when a thin film made of the thermoelectric semiconductor composition is annealed or the like to cause crystal growth of the thermoelectric semiconductor fine particles. The heat-resistant resin is preferably a polyamide resin, a polyamideimide resin, a polyimide resin, or an epoxy resin, because it has higher heat resistance and does not adversely affect the crystal growth of the thermoelectric semiconductor particles in the thin film, and more preferably a polyamide resin, a polyamideimide resin, or a polyimide resin, because it has excellent flexibility. When a polyimide film is used as the substrate described later, a polyimide resin is more preferable as the heat-resistant resin, because of the adhesion to the polyimide film. In the present invention, the polyimide resin is a general term for polyimide and its precursor.
[0043] The heat-resistant resin preferably has a decomposition temperature of 300° C. or higher. If the decomposition temperature is within the above range, the resin can maintain its flexibility without losing its function as a binder, even when a thin film made of the thermoelectric semiconductor composition is annealed, as described below.
[0044] The heat-resistant resin preferably has a mass loss rate of 10% or less, more preferably 5% or less, and even more preferably 1% or less at 300° C. as measured by thermogravimetry (TG). If the mass loss rate is within the above range, the thermoelectric element layer can maintain its flexibility without losing its function as a binder, even when a thin film made of the thermoelectric semiconductor composition is annealed, as described below.
[0045] The amount of the heat-resistant resin in the thermoelectric semiconductor composition is 0.1 to 40% by mass, preferably 0.5 to 20% by mass, more preferably 1 to 20% by mass, and further preferably 2 to 15% by mass. When the amount of the heat-resistant resin is within the above range, the resin functions as a binder for the thermoelectric semiconductor material, making it easier to form a thin film, and a film having both high thermoelectric performance and film strength can be obtained.
[0046] (Ionic Liquid) The ionic liquid used in the present invention is a molten salt formed by combining a cation and an anion, and refers to a salt that can exist in a liquid state in any temperature range of -50 to 500°C. Ionic liquids have characteristics such as extremely low vapor pressure and non-volatility, excellent thermal stability and electrochemical stability, low viscosity, and high ionic conductivity, and therefore can effectively suppress the reduction in electrical conductivity between thermoelectric semiconductor particles as a conductive auxiliary. In addition, ionic liquids exhibit high polarity based on an aprotic ionic structure and have excellent compatibility with heat-resistant resins, so that the electrical conductivity of the thermoelectric element layer can be made uniform.
[0047] The ionic liquid may be a known or commercially available one. For example, a mixture of a cationic component such as a pyridinium, pyrimidinium, pyrazolium, pyrrolidinium, piperidinium, imidazolium, etc., a nitrogen-containing cyclic cationic compound and a derivative thereof; an amine-based cation of tetraalkylammonium and a derivative thereof; a phosphine-based cation such as phosphonium, trialkylsulfonium, tetraalkylphosphonium, etc. and a derivative thereof; a lithium cation and a derivative thereof; and a mixture of a Cl - , AlCl4 - , Al2Cl7 - , ClO4 - Chloride ions such as Br - bromide ions, such as I - Iodide ions such as BF4 - , PF6 - Fluoride ions such as F(HF) n - Halide anions such as NO3 - , CH3COO- , CF3COO - , CH3SO3 - , CF3SO3 - , (FSO2)2N - , (CF3SO2)2N - , (CF3SO2)3C - , AsF6 - , SbF6 - , NbF6 - , TaF6 - , F(HF)n - , (CN)2N - , C4F9SO3 - , (C2F5SO2)2N - , C3F7COO - , (CF3SO2)(CF3CO)N - and an anion component such as the above.
[0048] Among the above ionic liquids, from the viewpoints of high temperature stability, compatibility with thermoelectric semiconductor particles and resins, and suppression of a decrease in the electrical conductivity of the gaps between thermoelectric semiconductor particles, it is preferable that the cationic component of the ionic liquid contains at least one selected from pyridinium cations and derivatives thereof, and imidazolium cations and derivatives thereof. It is preferable that the anionic component of the ionic liquid contains a halide anion, and Cl - , Br - and I - It is more preferable that the composition contains at least one selected from the following:
[0049] Specific examples of ionic liquids in which the cationic component contains a pyridinium cation and a derivative thereof include 4-methyl-butylpyridinium chloride, 3-methyl-butylpyridinium chloride, 4-methyl-hexylpyridinium chloride, 3-methyl-hexylpyridinium chloride, 4-methyl-octylpyridinium chloride, 3-methyl-octylpyridinium chloride, 3,4-dimethyl-butylpyridinium chloride, 3,5-dimethyl-butylpyridinium chloride, 4-methyl-butylpyridinium tetrafluoroborate, 4-methyl-butylpyridinium hexafluorophosphate, 1-butyl-4-methylpyridinium bromide, 1-butyl-4-methylpyridinium hexafluorophosphate, and 1-butyl-4-methylpyridinium iodide. Of these, 1-butyl-4-methylpyridinium bromide, 1-butyl-4-methylpyridinium hexafluorophosphate, and 1-butyl-4-methylpyridinium iodide are preferred.
[0050] Specific examples of ionic liquids in which the cationic component contains an imidazolium cation and a derivative thereof include [1-butyl-3-(2-hydroxyethyl)imidazolium bromide], [1-butyl-3-(2-hydroxyethyl)imidazolium tetrafluoroborate], 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium bromide, 1-butyl-3-methylimidazolium chloride, 1-hexyl-3-methylimidazolium chloride, 1-octyl-3-methylimidazolium chloride, 1-decyl-3-methylimidazolium chloride, and 1-decyl-3-methylimidazolium chloride. Examples of the imidazolium bromide include 1-dodecyl-3-methylimidazolium chloride, 1-tetradecyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-hexyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium hexafluorophosphate, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-methyl-3-butylimidazolium methyl sulfate, and 1,3-dibutylimidazolium methyl sulfate. Among these, [1-butyl-3-(2-hydroxyethyl)imidazolium bromide] and [1-butyl-3-(2-hydroxyethyl)imidazolium tetrafluoroborate] are preferred.
[0051] The above ionic liquid has an electrical conductivity of 10 -7 S / cm or more is preferable, and 10 -6 If the electrical conductivity is in the above range, the thermoelectric semiconductor material can effectively suppress the decrease in electrical conductivity between the thermoelectric semiconductor particles as a conductive auxiliary.
[0052] The ionic liquid preferably has a decomposition temperature of 300° C. or higher. If the decomposition temperature is within the above range, the effect as a conductive auxiliary agent can be maintained even when a thin film of a thermoelectric element layer made of the thermoelectric semiconductor composition is annealed, as described below.
[0053] The ionic liquid preferably has a mass loss rate of 10% or less, more preferably 5% or less, and even more preferably 1% or less, at 300° C. as measured by thermogravimetry (TG). If the mass loss rate is within the above range, the ionic liquid can maintain its effect as a conductive auxiliary even when a thin film of a thermoelectric element layer made of the thermoelectric semiconductor composition is annealed, as described below.
[0054] The amount of the ionic liquid in the thermoelectric semiconductor composition is preferably 0.01 to 50% by mass, more preferably 0.5 to 30% by mass, and further preferably 1.0 to 20% by mass. When the amount of the ionic liquid is within the above range, a decrease in electrical conductivity is effectively suppressed, and a film having high thermoelectric performance is obtained.
[0055] (Inorganic ionic compounds) The inorganic ionic compound used in the present invention is a compound composed of at least a cation and an anion. The inorganic ionic compound is a solid at room temperature, has a melting point at any temperature in the temperature range of 400 to 900°C, and has characteristics such as high ionic conductivity, so that it can suppress the decrease in electrical conductivity between thermoelectric semiconductor particles as a conductive auxiliary.
[0056] As the cation, a metal cation is used. Examples of the metal cation include alkali metal cations, alkaline earth metal cations, typical metal cations and transition metal cations, with alkali metal cations and alkaline earth metal cations being more preferred. Examples of alkali metal cations include Li + , Na + , K + , Rb + , Cs + and Fr + etc. Examples of alkaline earth metal cations include Mg 2+ , Ca 2+ , Sr 2+ and Ba 2+ etc.
[0057] The anion may be, for example, F - , Cl - , Br - , I - , O.H. - , C.N. - , NO3 - , NO2 - , ClO - , ClO2 - , ClO3 - , ClO4 - , CrO4 2- , HSO4 - , SCN - , BF4 - , PF6 - etc.
[0058] The inorganic ionic compound may be any known or commercially available inorganic ionic compound. For example, a cationic component such as potassium cation, sodium cation, or lithium cation and a Cl - , AlCl4 - , Al2Cl7 - , ClO4 - Chloride ions such as Br - bromide ions, such as I - Iodide ions such as BF4 - , PF6 - Fluoride ions such as F(HF) n - Halide anions such as NO3 - , O.H. - , C.N. - and an anion component such as the above.
[0059] Among the above inorganic ionic compounds, from the viewpoints of high temperature stability, compatibility with thermoelectric semiconductor particles and resin, and suppression of decrease in electrical conductivity in the gaps between thermoelectric semiconductor particles, it is preferable that the cationic component of the inorganic ionic compound contains at least one selected from potassium, sodium, and lithium. Also, it is preferable that the anionic component of the inorganic ionic compound contains a halide anion, and Cl is preferably 0.01 to 0.01. - , Br - , and I -It is more preferable that the composition contains at least one selected from the following:
[0060] Specific examples of inorganic ionic compounds in which the cationic component contains a potassium cation include KBr, KI, KCl, KF, KOH, K2CO3, etc. Among these, KBr and KI are preferred. Specific examples of inorganic ionic compounds in which the cationic component contains a sodium cation include NaBr, NaI, NaOH, NaF, Na2CO3, etc. Among these, NaBr and NaI are preferred. Specific examples of inorganic ionic compounds in which the cationic component contains a lithium cation include LiF, LiOH, LiNO3, etc. Among these, LiF and LiOH are preferred.
[0061] The above inorganic ionic compounds have an electrical conductivity of 10 -7 S / cm or more is preferable, and 10 -6 If the electrical conductivity is within the above range, the thermoelectric semiconductor material can effectively suppress the decrease in electrical conductivity between the thermoelectric semiconductor particles as a conductive auxiliary.
[0062] The inorganic ionic compound preferably has a decomposition temperature of 400° C. or higher. If the decomposition temperature is within the above range, the effect as a conductive auxiliary agent can be maintained even when a thin film of a thermoelectric element layer made of the thermoelectric semiconductor composition is annealed, as described below.
[0063] The inorganic ionic compound preferably has a mass loss rate of 10% or less, more preferably 5% or less, and even more preferably 1% or less at 400° C. as measured by thermogravimetry (TG). If the mass loss rate is within the above range, the compound can maintain its effect as a conductive auxiliary even when a thin film of a thermoelectric element layer made of the thermoelectric semiconductor composition is annealed, as described below.
[0064] The amount of the inorganic ionic compound in the thermoelectric semiconductor composition is preferably 0.01 to 50 mass%, more preferably 0.5 to 30 mass%, and further preferably 1.0 to 10 mass%. When the amount of the inorganic ionic compound is within the above range, the decrease in electrical conductivity can be effectively suppressed, and as a result, a film with improved thermoelectric performance can be obtained. In addition, when an inorganic ionic compound and an ionic liquid are used in combination, the total content of the inorganic ionic compound and the ionic liquid in the thermoelectric semiconductor composition is preferably 0.01 to 50 mass%, more preferably 0.5 to 30 mass%, and even more preferably 1.0 to 10 mass%.
[0065] (Other additives) In addition to the components other than those described above, the thermoelectric semiconductor composition used in the present invention may further contain, as necessary, other additives such as dispersants, film-forming assistants, light stabilizers, antioxidants, tackifiers, plasticizers, colorants, resin stabilizers, fillers, pigments, conductive fillers, conductive polymers, curing agents, etc. These additives may be used alone or in combination of two or more.
[0066] (Method for preparing thermoelectric semiconductor composition) The method for preparing the thermoelectric semiconductor composition used in the present invention is not particularly limited, and the thermoelectric semiconductor composition may be prepared by mixing and dispersing the thermoelectric semiconductor fine particles, the heat-resistant resin, and the ionic liquid and / or inorganic ionic compound, as well as the other additives as necessary and a solvent, using a known method such as an ultrasonic homogenizer, a spiral mixer, a planetary mixer, a disperser, or a hybrid mixer. Examples of the solvent include toluene, ethyl acetate, methyl ethyl ketone, alcohol, tetrahydrofuran, methylpyrrolidone, ethyl cellosolve, and the like. These solvents may be used alone or in combination of two or more. The solid content concentration of the thermoelectric semiconductor composition is not particularly limited as long as the composition has a viscosity suitable for coating.
[0067] The thin film of the thermoelectric element layer made of the thermoelectric semiconductor composition can be formed by filling the openings of the pattern frame used in the present invention with the thermoelectric semiconductor composition and drying it. By forming the thermoelectric element layer in this manner, a thermoelectric element layer with excellent shape controllability that reflects the shape of the openings of the pattern layer can be obtained.
[0068] The thickness of the thin film of the thermoelectric element layer made of the thermoelectric semiconductor composition is not particularly limited, but from the viewpoints of thermoelectric performance and film strength, it is preferably 100 nm to 1000 μm, more preferably 1 to 600 μm, even more preferably 10 to 400 μm, and particularly preferably 10 to 300 μm.
[0069] <Pattern frame peeling process> The pattern frame peeling step is a step of peeling off only the pattern frame from the substrate, with respect to the pattern frame including the thermoelectric element layer formed in the thermoelectric element layer forming step. For example, in Fig. 1(d), the pattern frame 2 made of stainless steel 2' is peeled off from the substrate 1, with the P-type thermoelectric element layer 4b and the N-type thermoelectric element layer 4a formed in the opening 3, and the P-type thermoelectric element layer 4b and the N-type thermoelectric element layer 4a remaining on the substrate 1. The peeling method is not particularly limited and may be any known method as long as the peeling of the pattern frame does not impair the shape of the thermoelectric element layer, does not cause minor damage to the surface of the thermoelectric element layer, and does not result in a decrease in thermoelectric performance. The pattern frame peeling step may also be performed after the annealing step described below as long as the above conditions are satisfied after the peeling.
[0070] Annealing process The manufacturing method of the present invention preferably includes a step of annealing the thermoelectric element layer. The annealing step is a step of further heat treating the thermoelectric element layer after drying in the thermoelectric semiconductor composition drying step. By carrying out the annealing treatment, the thermoelectric performance can be stabilized and the thermoelectric semiconductor particles in the thermoelectric element layer (thin film) can be grown as crystals, thereby further improving the thermoelectric performance.
[0071] The annealing treatment is not particularly limited, but is usually carried out under an inert gas atmosphere such as nitrogen or argon, under a reducing gas atmosphere, or under vacuum conditions with the gas flow rate controlled, and depends on the heat-resistant resin, ionic liquid, inorganic ionic compound, and the heat-resistant temperature of the substrate, etc., used. When a substrate having high heat resistance such as the above-mentioned glass, silicon, ceramic, or metal is used, the annealing temperature is usually 250 to 650°C for several minutes to several tens of hours, and preferably 250 to 600°C for several minutes to several tens of hours. When a resin film such as the aforementioned polyimide film, polyamide film, polyetherimide film, polyaramid film, or polyamideimide film is used as the substrate, the heating is usually performed at 100 to 450°C for several minutes to several tens of hours, preferably at 150 to 400°C for several minutes to several tens of hours, more preferably at 200 to 375°C for several minutes to several tens of hours, and even more preferably at 250 to 350°C for several minutes to several tens of hours.
[0072] <Thermoelectric element layer peeling process> The manufacturing method of the present invention may include a step of peeling off the chips constituting the thermoelectric element layer after the annealing treatment. The thermoelectric element layer peeling step is a step of peeling off the thermoelectric element layer as chips constituting the thermoelectric element layer from the substrate after annealing the thermoelectric element layer.
[0073] In the thermoelectric element layer peeling step, the method for peeling off the chips constituting the thermoelectric element layer from the substrate is not particularly limited as long as it is a method that allows peeling, and is performed by a known method, and the chips may be peeled off directly from the substrate, or the chips constituting the multiple thermoelectric element layers may be transferred collectively onto another substrate or onto an electrode of another substrate using the above-mentioned transfer substrate. This can be appropriately adjusted depending on the configuration of the thermoelectric conversion element.
[0074] The chips constituting the thermoelectric element layer have excellent shape controllability. From the viewpoint of improving thermoelectric performance, it is preferable that the chips are configured to be used in a π-type or in-plane type thermoelectric conversion element and are connected via electrodes. Here, when constructing a π-type thermoelectric conversion element, for example, a pair of electrodes spaced apart from each other are provided on a substrate, a chip constituting a P-type thermoelectric element layer is provided on one electrode, and a chip constituting an N-type thermoelectric element layer is provided on the other electrode, also spaced apart from each other, and the upper surfaces of the chips constituting both thermoelectric element layers are electrically connected in series to the electrodes on the opposing substrate. From the viewpoint of efficiently obtaining high thermoelectric performance, it is preferable to use a plurality of pairs of chips constituting a P-type thermoelectric element layer and chips constituting an N-type thermoelectric element layer, which are electrically connected in series, with the electrodes of the opposing substrates interposed therebetween. Similarly, when configuring an in-plane type thermoelectric conversion element, for example, one electrode is provided on a substrate, and a chip that configures a P-type thermoelectric element layer on the surface of the electrode and a chip that configures an N-type thermoelectric element layer on the surface of the electrode are provided so that the side surfaces of both chips (for example, surfaces perpendicular to the substrate) are in contact with or spaced apart from each other, and the electrodes are interposed between them and the chips are electrically connected in series (including a pair of extraction electrodes) in the in-plane direction of the substrate. From the viewpoint of efficiently obtaining high thermoelectric performance, it is preferable that in this configuration, the same number of chips that configure a plurality of P-type thermoelectric element layers and chips that configure an N-type thermoelectric element layer are alternately connected in series electrically in the in-plane direction of the substrate with electrodes interposed between them.
[0075] According to the method for producing a thermoelectric conversion element of the present invention, it is possible to improve the shape controllability of the thermoelectric element layer by a simple method. The configuration of the thermoelectric conversion element is preferably a configuration used for a π-type or in-plane type thermoelectric conversion element. In either configuration, high integration of the thermoelectric conversion element can be realized.
[0076] [Thermoelectric conversion element] The thermoelectric conversion element obtained by the manufacturing method of the present invention includes a thermoelectric element layer obtained by going through the steps of providing a pattern frame having an opening on the substrate, filling the opening with the thermoelectric semiconductor composition, drying the thermoelectric semiconductor composition filled in the opening to form a thermoelectric element layer, and peeling off the pattern frame from the substrate, in a method for manufacturing a thermoelectric conversion element including a thermoelectric element layer on a substrate, the steps being: providing a pattern frame having an opening on the substrate; filling the opening with the thermoelectric semiconductor composition; drying the thermoelectric semiconductor composition filled in the opening to form a thermoelectric element layer; and peeling off the pattern frame from the substrate.
[0077] (Thermoelectric element layer) The thermoelectric element layer of the thermoelectric conversion element obtained by the manufacturing method of the present invention has a concave recess on its upper surface. The thermoelectric element layer is formed by filling the openings of the pattern frame with a thermoelectric semiconductor composition containing a thermoelectric semiconductor material, and then removing volatile components in the thermoelectric semiconductor composition by drying, so that the surface of the thermoelectric element layer corresponding to the openings of the openings on the opposite side of the pattern frame from the substrate side is not flat but recessed. For example, in (d) of FIG. 1, the upper surface portions of the N-type thermoelectric element layer 4a and the P-type thermoelectric element layer 4b may be recessed. The shape and dimensions of the concave depressions are not constant because they depend on the viscosity, volatile components, drying conditions, etc. of the thermoelectric semiconductor composition, but typically the concave depressions are 1 to 30% of the thickness of the thermoelectric element layer.
[0078] The thermoelectric element layer of the thermoelectric conversion element obtained by the manufacturing method of the present invention may have stripe-like scratches extending in a direction intersecting with the substrate on its side. This is presumably because the thermoelectric element layer is formed by filling the opening of the pattern frame with a thermoelectric semiconductor composition containing a thermoelectric semiconductor material, then drying to form a thermoelectric element layer, and then peeling the pattern frame from the substrate, and therefore, when the pattern frame is peeled off, physical interactions such as friction occur at the interface between the wall surface in the opening of the pattern frame and the side of the thermoelectric element layer, and after peeling, stripe-like scratches extending in a direction intersecting with the substrate are formed on the side of the thermoelectric element layer obtained on the substrate. For example, in (d) of FIG. 1, stripe-like scratches extending in a direction intersecting with the substrate are generated on either of the side portions of the N-type thermoelectric element layer 4a and the P-type thermoelectric element layer 4b. The length, width, number, etc. of the streak-like scratch marks are not constant because they depend on the surface hardness, surface roughness, and peeling conditions (peeling direction, peeling speed, etc.) of the wall surface within the opening of the pattern frame; however, the length of the streak-like scratch marks is usually 100 nm to 500 μm. [Industrial Applicability]
[0079] According to the method for producing a thermoelectric conversion element of the present invention, a thermoelectric conversion element having a thermoelectric element layer with excellent shape controllability and capable of being highly integrated can be obtained by a simple production method. At the same time, since the variation in resistance value of each of a plurality of P-type thermoelectric element layer-N-type thermoelectric element layer pairs can be suppressed, an improvement in the production yield can be expected. Furthermore, the thermoelectric conversion element obtained by the method for producing a thermoelectric conversion element of the present invention can be made thin (small and lightweight). By forming a thermoelectric conversion element obtained by the above-mentioned method for producing a thermoelectric conversion element into a module, it is possible to apply the thermoelectric conversion element to power generation applications in which exhaust heat from various combustion furnaces such as factories, waste combustion furnaces, and cement combustion furnaces, exhaust heat from automobile combustion gases, and exhaust heat from electronic devices are converted into electricity. As cooling applications, in the field of electronic devices, it is possible to apply the thermoelectric conversion element to temperature control of various sensors such as CPUs (Central Processing Units) used in smartphones and various computers, image sensors such as CMOS (Complementary Metal Oxide Semiconductor Image Sensors) and CCD (Charge Coupled Devices), and further, MEMS (Micro Electro Mechanical Systems) and other light receiving elements. [Explanation of symbols]
[0080] 1: Substrate 2: Pattern frame 2': Stainless steel 3s: opening 3d: Opening depth (pattern frame thickness) 3: Opening 4a: N-type thermoelectric element layer 4b: P type thermoelectric element layer 11a: Substrate 11b: Opposing substrate 12a: Electrode 12b: Counter electrode 14a: N-type thermoelectric element layer 14b: P-type thermoelectric element layer
Claims
1. A method for producing a thermoelectric conversion element including a thermoelectric element layer made of a thermoelectric semiconductor composition including a thermoelectric semiconductor material on a substrate, comprising: providing a pattern frame having an opening on the substrate; filling the opening with the thermoelectric semiconductor composition; a step of drying the thermoelectric semiconductor composition filled in the opening to form a thermoelectric element layer, and a step of peeling off the pattern frame from the substrate, A release layer is included on the wall surface of the opening of the pattern frame, A method for manufacturing a thermoelectric conversion element.
2. The method for manufacturing a thermoelectric conversion element according to claim 1 , further comprising the step of subjecting the thermoelectric element layer to an annealing treatment.
3. The method for producing a thermoelectric conversion element according to claim 2, wherein the annealing temperature is 250 to 600°C.
4. The method for producing a thermoelectric conversion element according to claim 2 or 3, further comprising the step of peeling off the chips constituting the thermoelectric element layer after the annealing treatment.
5. 5. The method for producing a thermoelectric conversion element according to claim 1, wherein the substrate is a polyimide film, a polyamide film, a polyetherimide film, a polyaramid film, or a polyamideimide film.
6. The method for manufacturing a thermoelectric conversion element according to any one of claims 1 to 5, wherein the pattern frame comprises stainless steel, copper, aluminum, or iron.
7. The method for manufacturing a thermoelectric conversion element according to claim 1 , wherein the pattern frame includes a ferromagnetic material.
8. The method for manufacturing a thermoelectric conversion element according to any one of claims 1 to 7, further comprising the step of fixing the pattern frame to the substrate using a magnet.
9. The method for producing a thermoelectric conversion element having a substrate according to any one of claims 1 to 8, wherein the thermoelectric semiconductor composition further contains a heat-resistant resin, and an ionic liquid and / or an inorganic ionic compound.
10. The method for producing a thermoelectric conversion element according to any one of claims 1 to 9, wherein the thermoelectric semiconductor material is a bismuth-tellurium-based thermoelectric semiconductor material, a telluride-based thermoelectric semiconductor material, an antimony-tellurium-based thermoelectric semiconductor material, or a bismuth selenide-based thermoelectric semiconductor material.
11. The method for producing a thermoelectric conversion element according to claim 9 , wherein the heat-resistant resin is a polyimide resin, a polyamide resin, a polyamideimide resin, or an epoxy resin.
12. The method for producing a thermoelectric conversion element according to any one of claims 1 to 11, wherein the shape of the opening is one or more shapes selected from the group consisting of an irregular shape, a polyhedral shape, a truncated cone shape, an elliptical truncated cone shape, a cylindrical shape, and an elliptical cylindrical shape.
Citation Information
Patent Citations
Manufacture of thermoelectric transfer element
JP1997116199A
Manufacturing method of peltier module
JP1998215005A
Pattern formation
JP2000233560A
Asymmetric thermoelectric module and manufacturing method of the same
JP2012064913A
Method of manufacturing thermoelectric conversion element
JP2013251333A